A escola como componente da rede social de apoio à paternidade na adolescência - Soares, Tatiane Machado da Silva (2010)
The present study had as objective to know the perceptions of adolescent fathers about school as a social network of support for paternity in the adolescency. This is a study with qualitative approach, which used as a theoretical reference the Sluzki´s concept on social networks. It was developed with five teenage parents: two were students of a local public school in the city of Pelotas and three were participants in a multicentric research called Support Network to Paternity in Adolescency. After the consent of participants, the collecting data began, which has occurred in the months of August and September of 2009, at home of each parent teenagers. The application of a semistructured questionnaire with open questions was used as a collection technique. The interviews were recorded, faithfully transcribed, analyzed and organized into themes. It was found that teenage parents escaped from the school before the paternity because of the need to work and obtain financial resources to support themselves. None of them had knowledge about social support networks and also unaware of their rights as citizens and students, which are described in the Law of Directives and Bases of Education. The school, in the view of each of them, also showed no concern or encouragement to help them stay in school. It is necessary to disclose these parents their rights as citizens, because only through information and education is that they could reach their goals as men, as parents and as citizens.